Literasi sains dan penguasaan konsep siswa setelah pembelajaran sistem ekskresi menggunakan pedoman praktikum berbasis literasi sains - Rina Sumarni; Soesy Asiah Soesilawati; Yayan Sanjaya (Department of Biology Education, Universitas Pendidikan Indonesia, 2021)
Scientific literacy is very important for students. The purpose of this study is to analyze the student's scientific literacy and conceptual mastery after learning the excretion system using scientific literacy-based practical guidelines. In this study, there was one class consisting of 34 students. Before learning, students do pre-test questions regarding scientific literacy, after completing learning, students work on a post-test questions with the same question and add concept mastery questions. This research used a pre-experiment method with one group pre-test post-test design. The instrument used was a matter of scientific literacy and conceptual mastery questions. The results of this study indicate that the student's scientific literacy after learning the excretion system using science literacy–based practicum guidelines is in the high category with an average value of 70,06. Scientific literacy abilities are based on aspects of competence and aspects of scientific literacy knowledge. Then overall the students have mastered the conceptual mastery of the material that has been studied well.